Pengaruh Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT. ABSH Fagrance Creations - Fadilah Dewi Sinta; Khotim Fadhli (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze the influence of work discipline and job satisfaction on employee performance at PT ABSH Fragrance Creation Jombang. The background of this research focuses on the crucial role of these two factors in enhancing employee productivity and work effectiveness. The approach used is quantitative, with data collected through questionnaires distributed to 40 employees. The analysis results indicate that work discipline does not have a significant impact on employee performance, with a significance value of 0.185. Meanwhile, job satisfaction is proven to have a significant effect on employee performance, with a significance value of 0.000. Multiple regression analysis reveals that, simultaneously, both independent variables contribute significantly to employee performance, with a coefficient of determination (adjusted R²) of 0.785. This means that 78.5% of the variation in employee performance can be explained by work discipline and job satisfaction. These findings highlight the importance of improving job satisfaction as a key strategy to enhance employee performance in the company. This study is expected to provide recommendations for management in formulating more effective policies to improve employee satisfaction and performance.